Terpenoids From the Coral-Derived Fungus Trichoderma harzianum (XS-20090075) Induced by Chemical Epigenetic Manipulation - Shi, Ting; Shao, Chang-Lun; Liu, Yang; Zhao, Dong-Lin; Cao, Fei; Fu, Xiu-Mei; Yu, Jia-Yin; Wu, Jing-Shuai; Zhang, Zhen-Kun; Wang, Chang-Yun (Frontiers in Microbiology, 2020)
The soft coral-derived fungus Trichoderma harzianum (XS-20090075) was found to be a potential strain to produce substantial new compounds in our previous study. In order to explore its potential to produce more metabolites, chemical epigenetic manipulation was used on this fungus to wake its sleeping genes, leading to the significant changes of its secondary metabolites by using a histone deacetylase (HDAC) inhibitor. The most obvious difference was the original main products harziane diterpenoids were changed into cyclonerane sesquiterpenoids. Three new terpenoids were isolated from the fungal culture treated with 10 μM sodium butyrate, including cleistanthane diterpenoid, harzianolic acid A (1), harziane diterpenoid, harzianone E (2), and cyclonerane sesquiterpenoid, 3,7,11-trihydroxy-cycloneran (3), together with 11 known sesquiterpenoids (4–14). The absolute configurations of 1–3 were determined by single-crystal X-ray diffraction, ECD and OR calculations, and biogenetic considerations. This was the first time to obtain cleistanthane diterpenoid and africane sesquiterpenoid from genus Trichoderma, and this was the first chlorinated cleistanthane diterpenoid. These results demonstrated that the chemical epigenetic manipulation should be an efficient technique for the discovery of new secondary metabolites from marine-derived fungi.